A Framework for the Examination of Relational Ethics: An Interactionist Perspective - Pelton, Lou E. (Journal of business ethics, 1999)
Despite the widespread agreement that the ontology of the marketing discipline is exchange, marketing ethics researchers have largely adopted a monadic viewpoint of ethical decision making. In this research, an interactionist approach is adopted in order to introduce a dyadic perspective of un/ethical decision making. The dyadic model includes each channel member's individual, situational and decision process factors linked by relationalism, an emerging paradigm in marketing channels. Relationalism is represented as a discriminating variable between perceived ethical dilemma and decision behaviour. Finally, a number of theoretical propositions are presented and future research directions are discussed.